Comparison to Kralicek DF Indicators and Altman Z-Score Model for Serbian Metal Industry - Lončarević, Svjetlana (International Journal of Industrial Engineering and Management, 2015)
This study compares the results of two instruments of strategic controlling. The research was based on a sample of several companies in the metal-industry sector of the Serbian economy. Using a software tool "Scorex.biz Analayzer" and publicly available data of annual financial statements, interdependence and similarity of the results obtained from Kralicek DF indicators and Altman Z-Score model will be shown. Controlling is one of the functions of management, which increases its efficiency, effectiveness and ability to adapt to changes. It is tool used to support management of each company, made of system methods and tools aimed to show business efficiency. Specifically, controlling includes the planning, coordination and control activities, and it was developed due to the increasingvolume of business information. As a result, controlling is expected to provide expert and substantiated opinions, recommendations and conclusions for management so it can be familiar with the issues of running the business, as well as possible future risks and effects of potential businessdecisions. Because it covers the entire range of related activities and requires knowledge from different functional areas (finance, accounting, information technology, organizations etc.) controlling is important business supporting processes within the company, primarily focused to company internal managing stuff. Article history: Received (15.11.2015); Revised (21.12.2015); Accepted (27.12.2015)